PENGARUH STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN - Zaki Imadudin; Fifi Swandari; Redawati (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
The purpose of this study is to examine the impact of capital structure on corporate performance after crisis 2008. DAR and DER are used as independent variables and ROA and ROE are used as dependent variables. Two variables are used as control variables namely size and sales. The population in this study is index LQ 45 which are listed in Indonesia Stock Exchange during 2009-2012. Regression analysis were used to test the impact of capital structure on corporate performance. The result shows that DAR has impact positive but not significant with ROA and negative but not significant with ROE while DER has negative but not significant with ROA dan positive but not significant with ROE. Size has negative but not significant with ROA and ROE and Sales has positive significant with ROA and ROE